Antibacterial Activity of Ethanol Extract from Green Spinach Leaves (Amaranthus viridis) Against Propionibacterium Acnes - Alfadhila Dwinanda Revalina; Anita Ratna Dilla; Andi Zsazsa Rafiatul Mukhlis (Jurnal Riset Kefarmasian Indonesia, 2026)
Acne is a common chronic skin disorder among adolescents in Indonesia, with a prevalence of approximately 80–85%, particularly in individuals aged 15–18 years. One of the main microorganisms associated with acne pathogenesis is Propionibacterium acnes. This study aimed to evaluate the antibacterial activity of the ethanol extract of green spinach (Amaranthus viridis) leaves against P. acnes. This experimental study was conducted using a well diffusion method. The green spinach leaf extract was prepared through maceration using 96% ethanol as the extraction solvent. Phytochemical screening was performed to identify the presence of bioactive compounds, and antibacterial activity was assessed at extract concentrations of 50%, 60%, and 70%, with clindamycin used as a positive control and sterile distilled water as a negative control. The phytochemical screening results showed that the ethanol extract contained flavonoids, tannins, and saponins. However, the antibacterial assay demonstrated that the extract at all tested concentrations did not produce inhibition zones against P. acnes. In contrast, clindamycin produced a clear inhibition zone with a diameter of 19.25 mm, while the negative control showed no inhibitory effect. These findings indicate that, under the experimental conditions applied in this study, the ethanol extract of green spinach leaves does not exhibit antibacterial activity against P. acnes. Further investigations using higher extract concentrations, alternative extraction methods, or different solvents are necessary to explore the potential antibacterial properties of green spinach leaves more comprehensively.